THE FIGURES OF SPEECH IN VOGUE™S ADVERTISEMENTS - Aritonang, Helena; Ownie, Sri Juriati (LINGUISTICA, 2013)
ABSTRACT The objectives of this research were to describe the twelve types of figures of speech namely lexical metaphor, namely: metaphor, simile, personification, synecdoche, metonymy, symbol, allegory, overstatement, apostrophe, understatement, verbal irony and the one that dominant and also explain what does the dominant mean in Vogue™s advertisements. This research was conducted by using the qualitative and quantitative design. It took fifteen advertisements taken randomly from Vogue™s magazine which were published from October 2011 until January 2012. The result showed that there are only five figures of speech were used in the advertisements of Vogue™s magazine, they are : hyperbole, personification, simile, metaphor and allegory.